Inward foreign direct investment and trade openness in Vietnam: A nonlinear autoregressive distributed lag approach - Jen Yao Lee; Ya-Chuan Hsiao; Ngochien Bui; Tien-Thinh Nguyen (Economies, 2021)
This study aims to examine the asymmetric relationship between trade openness and FDI (foreign direct investment) inflows to Vietnam by using NARDL (nonlinear autoregressive distributed lag) during the period from 1997 to 2019. Our findings show that the influence of FDI on trade openness is asymmetric in the short-run and long-run. But the influence of trade openness on FDI is symmetric in the short-run and asymmetric in the long run.
Keywords: 330; ARDL model; foreign direct investment; NARDL model; political stability; tax rate; trade openness